Physical activity engagement and responses to exercise in plaque psoriasis: a multifactorial investigation of influential factors. (17th February 2022) - Enos, Clinton; Algrni, Khaled; Van Voorhees, Abby; Wilson, Patrick
Abstract: Background: Psoriasis may increase the risk of physical inactivity, but few studies have evaluated the etiology. Objective: To identify barriers to and predictors of physical activity in psoriasis. Methods: Twenty individuals with psoriasis (PsO) and 23 controls recorded activity with accelerometers and completed self-paced 20-min treadmill bouts. Questionnaires on self-efficacy for exercise (SEE), pruritus, and dermatology life quality index (DLQI) were completed. Psoriasis severity was measured via body surface area (BSA), psoriasis area and severity index (PASI), and investigator's global assessment (IGA). Results: No differences in moderate-vigorous activity existed between PsO and controls (ANCOVA means: 26 ± 4 versus 27 ± 4 min, p  = .802). Relative to controls, PsO selected treadmill speeds that were 13-18% slower and experienced more pruritus while exercising. Among the PsO group, PASI, BSA, IGA, and DLQI showed inverse correlations with vigorous activity (partial rhos= −0.55 to −0.62, p  < .05). Likewise, BSA, IGA, DLQI, and pruritus were inversely correlated with footsteps (partial rhos= −0.47 to −0.62, p  < .05). SEE was consistently positively correlated with activity levels among PsO (partial rhos ≥0.60 for moderate activity, vigorous activity, and footsteps). Conclusion: Individuals with extensive psoriasis and poorer SEE engage in less vigorous activity and take fewer footsteps. Among other factors, pruritus is a novel explanation.